Revisão sistemática: gamificação em smartphones para crianças em contextos educacionais e terapêuticos - Alves, Rodrigo Ribeiro; Lembor, Victor Hugo da Silva; Macedo, Alessandra Alaniz (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
Caregiver concerns about children’s excessive mobile device use potential include impacts on mental health, physical well-being, social development, and academic performance. Statistics like 60% of under-12s spending most of their time playing on phones, and 71% of Brazilian children aged 0-12 are playing games on smartphones contextualized caregiver’s concerns. Parents perceive the use of smartphones are unproductive and detrimental to children development. However, mobile technology in serious games may offer a productive and stimulating way to engage children and adults, ranging from academic learning to therapeutic support. Thanks to their effectiveness and accessibility, research on the use of mobile devices and serious games has gained significant prominence. This work is dedicated to surveying scientific productions in the literature on the use of mobile devices and serious games in educational and therapeutic contexts. In this article, a systematic review of works focused on the use of gamification in mobile devices for children in educational and therapeutic contexts is presented. The objective is to evaluate the extent to which this area has been explored and to understand the potential of using technological resources to aid in the development of these activities. The initial search across seven digital libraries, using filters for open-access publications between 2019 and 2024, yielded a total of 104 articles; however, only 8 were selected after removing duplicates, applying exclusion and inclusion criteria, screening by title and abstract, and full-text review. This review finds that techniques like rewards, feedback, and visual narratives effectively boost engagement and adherence. The study emphasizes tailoring gamification to task nature and combining extrinsic and intrinsic motivators. However, limitations include small sample sizes, short intervention durations, and methodological heterogeneity, hindering generalizability and long-term efficacy conclusions. Future research should involve larger, longer-term randomized trials and focus on specific populations.